Feminism and Couple Finance: Power as a Mediator Between Financial Processes and Relationship Outcomes. - LeBaron, Ashley B.; Holmes, Erin K.; Yorgason, Jeremy B.; Hill, E. Jeffrey; Allsop, David B. (Sex Roles, 2019)
Feminism is rarely used as a theoretical framework for couple finance research. The purposes of the present paper are (a) to discuss couple finance research in the context of feminism to encourage more frequent and explicit use of feminism in couple finance research, (b) to present a gender and couple finances model, and (c) to test this model with longitudinal dyadic data. Using actor-partner interdependence models (APIM) and data from 327 U.S. mixed-gender couples, relational power was explored as a potential mediator between four couple financial processes (earners of money, access to money, management of money, and conflict about money) and two relationship outcomes (relationship quality and relationship stability). Results suggest that couple financial processes are associated with relationship outcomes and with joint management as well as low conflict being key longitudinally. Additionally, although power may not play a mediating role, it appears to be connected to couple financial processes and relationship outcomes concurrently. Gender differences as well as both actor and partner effects are explored. This research has implications for researchers, clinicians, and educators. For example, clinicians may want to encourage their clients to use joint bank accounts, manage their money jointly, and minimize financial conflict. Gender, and therefore power, are inseparably tied to couple finances. When both spouses are involved in financial processes, partners tend to be more empowered, and relationship quality and stability tend to be higher.